A Review on Multi-Level Inverter Design Methodologies: Advancements and Applications (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this review paper we study Multi-Level Inverter Design Methodologies. Multilevel inverters continue to receive more and more attention because of their high voltage operation capability, low switching losses, high efficiency and low output of Electro Magnetic Interference (EMI). A multilevel inverter is a power electronic device that can provide the required amount of alternating voltage at the output using various reduced level DC voltages as an input. To produce AC voltage from DC voltage, a two-level inverter is mostly used. Thus, the use of a multilevel converter has increased in industrial and renewable energy applications, which require high-voltage and high output quality.